A comparison of photoautotrophic, heterotrophic, and mixotrophic growth for biomass production by the green alga Scenedesmus sp. (Chlorophyceae). Issue 3 (1st May 2018) - Kamalanathan, Manoj; Chaisutyakorn, Panjaphol; Gleadow, Roslyn; Beardall, John
Abstract: Substantial research has been devoted to testing the potential for algal-derived biofuels. However, because of the high cost and low biomass productivity of algal mass culture, this is not yet a commercial reality. Most research has focused on optimizing photoautotrophic cultivation of algal biomass. Other modes of growing algae such as heterotrophy and mixotrophy need to be investigated. Our objective was to compare the biomass productivity and the macromolecular pools of Scenedesmus sp. grown under photoautotrophic and heterotrophic conditions, and to expose the heterotrophic cultures to light after their growth slowed or ceased. We found that heterotrophy led to larger cells, faster growth rates, and denser cultures than photoautotrophically grown cultures. Exposing heterotrophically growing cells to light caused an immediate significant boost to growth rates and biomass production. As a result, biomass obtained through this process (mixotrophy) was double that of heterotrophically grown cultures, and three times greater than with photosynthetically grown cultures. Higher cellular carbohydrates and proteins were observed in mixotrophic cultures than in photoautotrophic ones. Despite these cellular changes, overall biomass and lipid productivity can be ranked as follows: mixotrophy > heterotrophy > photoautotrophy. This study provides promising leads for the use of molasses in algal biomass cultivation.